Multi-site comparison of factors influencing progress of African insecticide testing facilities towards an international Quality Management System certification - Sara Begg (Public Library of Science (PLoS), 2021)
Background Insecticidal mosquito vector control products are vital components of malaria control programmes. Test facilities are key in assessing the effectiveness of vector control products against local mosquito populations, in environments where they will be used. Data from these test facilities must be of a high quality to be accepted by regulatory authorities, including the WHO Prequalification Team for vector control products. In 2013–4, seven insecticide testing facilities across sub-Saharan Africa, with technical and financial support from Innovative Vector Control Consortium (IVCC), began development and implementation of quality management system compliant with the principles of Good Laboratory Practice (GLP) to improve data quality and reliability. Methods and principle findings We conducted semi-structured interviews, emails, and video-call interviews with individuals at five test facilities engaged in the IVCC-supported programme and working towards or having achieved GLP. We used framework analysis to identify and describe factors affeting progress towards GLP. We found that eight factors were instrumental in progress, and that test facilities had varying levels of control over these factors. They had high control over the training programme, project planning, and senior leadership support; medium control over infrastructure development, staff structure, and procurement; and low control over funding the availability and accessibility of relevant expertise. Collaboration with IVCC and other partners was key to overcoming the challenges associated with low and medium control factors. Conclusion For partnership and consortia models of research capacity strengthening, test facilities can use their own internal resources to address identified high-control factors. Project plans should allow additional time for interaction with external agencies to address medium-control factors, and partners with access to expertise and funding should concentrate their efforts on supporting institutions to address low-control factors. In practice, this includes planning for financial sustainability at the outset, and acting to strengthen national and regional training capacity.